The Irruption of Octeto Buenos Aires in the History of Tango. Social Reception Within the Context of the 1955 Change of Power-Structure in Argentina. (Revista Argentina de Musicología, 2018)
This paper investigates the impact produced by the music composed by Astor Piazzolla for the Octeto Buenos Aires (1955-1958) in the history of tango and its social reception in Argentina, taking into account that the coup d’etat of 1955 substantially modified the cultural field of the country. The lack of success of the Octet and the opposition it suffered were consequences not so much of the kind of music it played as of the particular situation of tango at that moment, of the change in cultural policies after the fall of democracy, of the change of social humor produced during the last years of the Perón regime and of the changes in the class conformation of Argentine society during those years, particularly because of the emergence of a middle-class identity, opposed to Peronism.